Citizenship, Immigration and Adult Education: The Role of Immigrant Service Organization in Building a Learning Community for Adult Immigrants - Shibao Guo (Adult Education Research Conference, 2004)
This paper examines the founding and historical development of an immigrant service organization in Canada, and the role it played in building a learning community for adult immigrants.